2014
DOI: 10.3109/02652048.2014.911377
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase-induced or citric acid-mediated cross-linking of whey proteins to tune the characteristics of subsequently desolvated sub-micron and nano-scaled particles

Abstract: Whey proteins were inter-connected either by the enzyme transglutaminase or citric acid and then desolvated with ethanol to generate particles. Both samples comprised of sub-micron (>300 nm) and nano-scaled (~100 nm) particles based on the hydrodynamic size measurements. Enzyme-induced cross-linking of proteins yielded more monodisperse particles and decreased the mean size of the major (nano-scaled) fraction of particles. Scanning electron microscopy images revealed a spherical morphology for all samples with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Citric acid can cross-link with the hydroxyls of polysaccharide, improve the compatibilization between the polymeric molecules, and improve the tensile strength of polysaccharide lms [19,20]. It was demonstrated that citric acid acts as a crosslinking agent in the lms and the result was consistent with some previous studies [20,21]. In addition, it was observed that when the amount of citric acid was more than 20%, the trend of tensile strength and elongation at break of the sample lms was relatively gentle.…”
Section: Mechanical Propertiessupporting
confidence: 87%
See 1 more Smart Citation
“…Citric acid can cross-link with the hydroxyls of polysaccharide, improve the compatibilization between the polymeric molecules, and improve the tensile strength of polysaccharide lms [19,20]. It was demonstrated that citric acid acts as a crosslinking agent in the lms and the result was consistent with some previous studies [20,21]. In addition, it was observed that when the amount of citric acid was more than 20%, the trend of tensile strength and elongation at break of the sample lms was relatively gentle.…”
Section: Mechanical Propertiessupporting
confidence: 87%
“…is is probably due to citric acid containing hydroxyl bonds, and therefore, the addition of citric acid will make this peak increase slightly. e appearance of the peak at 1740 cm −1 in the EAEP residue with citric acid added films is assigned to ester carbonyl bonds [21]. e intensity of these peaks is increasing with the addition of citric acid from 10% to 20%.…”
Section: Ftir Analysis Of Eaep Residuementioning
confidence: 95%
“…A small shoulder peak was also recognized around 1200 cm −1 . This peak is ascribed to C-O stretching of formed ester bonds [38][39][40][41]. Conversely, in Fig.…”
Section: Changes Of Chemical Structurementioning
confidence: 89%
“…Milled than in CA30-C film, indicating that SHP could have promoted citric acid decarboxylation on curing, as suggested by Yao, Wang, Ye, and Yang (2013), which would explain the unexpected effects of SHP on tensile properties and WVP of films in the present study. The increased peak at 1208 cm À1 in films with citric acid is ascribed to CeO stretching of formed ester bonds (Bagheri, Yarmand, Madadlou, & Mousavi, 2014;Groen & Roberts, 2001;Rhim et al, 2004). The presence of ester bonds may be indicated by the presence of a small shoulder around 1730 cm À1 in films with citric acid , which corresponds to ester C]O stretching vibration (Dastidar & Netravali, 2012;Shi et al, 2007;Wang et al, 2014).…”
Section: Fractionsmentioning
confidence: 95%